Identification of an unknown bacteria and evaluation of its potential use in bioremediation - Abu Bakar, Hassana; Edbeib, Mohamed Faraj; Abdul Hamid, Azzmer Azzar (UTM Press, 2016)
Enzymes are macromolecular biological catalysis that is important to speed up reaction. Enzymes can be found naturally from the microorganism such as bacteria, fungi and yeast which may not be genetically modified. In this perspectives, resorting to bioremediation to clean-up such environment may prove feasible and beneficial as microorganisms effective in degrading such substances. The liberation of excess halogenated compounds into the environment is becoming a major global issue, since the toxic contaminants tend to accumulate and persist in the biosphere. Some of the microbes that able to utilise these toxic compounds have been successfully isolated from the soil contaminated environment and were further charcterised. Apart from pollutant degradation, commercial enzyme like protease will be discussed that has potential for commercialisation in many manufacturing processes.